THE IMPORTANCE OF HEALTH EDUCATION OF IVA EXAMINATION (VISUAL ACETIC ACETIC INSPECTION) IN IMPROVING MOTHER KNOWLEDGE DETECTING EARLY CANCER SERVICES IN THE PUSKESMAS TUMINTING - Cheryn Alfa; Esther N Tamunu; Moudy Lombogia (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2019)
Background: Symptoms of cervical cancer are often not realized by women so that 70% of cases that occur are found in an advanced stage. This illustrates the still low active participation of women in screening or early detection of cervical cancer (Riksani, 2016). Aims: This study aims to determine the effect of health education on maternal knowledge about VIA examination (Visual Inspection of Acetic Acid) as early detection of cervical cancer in the working area of ​​Tuminting Health Center. Methods: This research method uses a One-Group pre-post test Design to 36 respondents were included in the inclusion criteria by accidental sampling. The measuring instrument used was a questionnaire. Data analysis using the Wilcoxon Signed Rank Test with a significance level (α) 0.05. Result: The results of this study were obtained from a statistical test of p = 0,000, meaning that the p-value ≤0.05. Conclusion: It was concluded that Ha was accepted, meaning that there was an influence of health education on maternal knowledge about the importance of VIA examination (Visual Inspection of Acetic Acid) as an effort to detect early cervical cancer in the working area of ​​Tuminting Puskesmas. Suggestions for further researchers to conduct a similar study with different research methods such as quasi-experiments with group control.